International Tourists’ Perceptions of Indonesia’s Tourism Attractiveness in the Post-Pandemic Era - Khalif, Kenzo Althaf; Ramdani, Dadan; Ibáñez, Maria José (Lembaga Penelitian dan Pendidikan, 2026)
The post-pandemic era has reshaped global tourism dynamics, influencing international tourists’ perceptions of destination attractiveness. Indonesia, as one of the leading tourism destinations in Southeast Asia, has implemented various recovery strategies to restore tourist confidence. This study aims to analyze international tourists’ perceptions of Indonesia’s tourism attractiveness after the COVID-19 pandemic. This research uses a quantitative approach through survey distribution to international tourists visiting Indonesia in 2023–2025. Data were analyzed using descriptive and inferential statistical methods. The findings show that cultural authenticity, natural landscape attractiveness, health safety assurance, and digital tourism services significantly influence tourist perceptions. However, infrastructure inequality and service quality inconsistency remain challenges. The study concludes that Indonesia’s tourism competitiveness in the post-pandemic era depends on integrated strategies combining sustainability, digital transformation, and service standardization. These findings contribute to tourism recovery policy development and destination marketing strategies in emerging tourism economies.